The Dynamics of Customary Land Dispute Resolution: Between Customary Law and Positive Law - Loso Judijanto (PT. Anagata Sembagi Education, 2025)
This research delves into the intricate interplay between traditional customary norms and formal statutory provisions in addressing indigenous land conflicts within Indonesia. Adopting a normative juridical framework, the study dissects the underlying legal doctrines, status, and operational realities of indigenous dispute resolution systems, while also scrutinising their interface with the formal mechanisms of state law. The analysis demonstrates that customary frameworks retain profound influence as mechanisms of land conflict resolution among native populations—an influence grounded in deep-rooted cultural authority, emphasis on communal restoration, and procedural informality. Nevertheless, the continued absence of consistent juridical acknowledgement and the lack of systemic integration within the national legal architecture have given rise to ambiguity and compromised the enforceability of traditional verdicts. Through an examination of statutory texts, judicial precedents, and scholarly discourse, the study exposes the pressing necessity for legal transformation—urging the institutionalisation of a more inclusive jurisprudential model that allows indigenous legal traditions to coexist and collaborate with state-driven legal protocols. It proposes the establishment of integrative frameworks, enhanced administrative mechanisms, and culturally responsive judicial interpretation as critical steps toward narrowing the legal divide and realising equitable access to justice in indigenous land affairs.